The Meanings We Choose: Hermeneutical Ethics, Indeterminacy and the Conflict of Interpretations. Edited by Charles H. Cosgrove - Davies, Eryl W. (The journal of theological studies, 2007)
In the postmodern context, the task of interpreting the meaning of the biblical text is highly contentious. Is the meaning that which was intended by the biblical author (or editor) or is it that which happens to take the reader's fancy—‘the meanings we choose’? If it is deemed to be the latter, is the door not opened to a veritable flood of impressionistic and idiosyncratic interpretations? At a time when there are almost as many interpretations of the biblical text as there are interpreters, do readers have a responsibility to choose one interpretation over another and, if so, what criteria should inform the decisions that they make? These are some of the issues raised in this thought-provoking and highly engaging volume., The book, ably edited by Charles H.